Processing of Organic Waste into Compost at the Hj. Sarwati Orphanage Yogyakarta - Eny Heriyati; Bakti Nur Ismuhajaroh (Altifani Journal: International Journal of Community Engagement, 2023)
One form of the tri dharma of higher education is community service. The purpose of the training activities for processing organic waste into compost at the Hj. Sarwati's goals are to foster a sense of sympathy and empathy as well as social care in society, to grow insight into processing organic waste into compost and to establish friendship with the orphanage children. This waste processing is motivated by the large amount of organic waste around the orphanage, so that organic waste that is not utilized can become a useful material. The activities of the orphanage children here besides studying and reciting the Koran are raising livestock and gardening, so the activity of processing organic waste into compost is very useful. This activity is carried out several days until the organic waste becomes compost. The stages of the activity include the provision of theory on how to process organic waste, waste collection and processing. After the waste treatment process is complete, the waste is left in the decomposer tub for the maturation process to become compost. The results of the compost will be used for plant fertilizer in the orphanage's garden.